?POND PRODUCTION OF THE FRESHWATER PRAWN, MACROBRACHIUM MALCOLMSONII IN SINDH, PAKISTAN - Yaqoob, Muhammad (Biological Sciences - PJSIR, 1999)
Freshwater prawn, Macrobrachiuin malcolmsonii (Milne Edwards) was cultured at two sites in Thatta, Sindh. The juvenile prawns were collected randomly from the lower belt or river Indus at Hilaya, were sorted and stocked in two ponds at Mirpur Sakro and two at Chilya after acclimatization. They were fed supplementary feed containing about 19% protein once daily. Hydrological characteristics (Dissolved Oxygen, pH and Temperature) of ponds were recorded regularly. The stocked prawns grew from a mean weight 01" 3.5,3.5,8.0 and 5.0 g to 55, 61,63 and 30 g in 251, 142,253 and 147 days respectively, under the conditions described herein. A production level or 765, 658, 754 and 217 kg ha:' respective to each pond was achieved.